Aktivitas Antiproliferasi Ekstrak Etanolik Herba Ciplukan (Physalis angulata L.) Terhadap Sel Hepar Tikus Betina Galur Sprague Dawley Terinduksi 7,12-Dimetilbenz[a]antrasena - Agusta Fauzi, Ilham; Amalia, Fikri; Sabila, Nurma; Hermawan, Adam; Ikawati, Muthi; Meiyanto, Edy (Lembaga Penelitian Universitas YARSI, 2011)
One of the natural materials as potentially efficacious chemopreventive agents are Ciplukan (Physalis angulata L.). Several previous studies reported that Physalis angulata L. herbs ethanolic extract (PEE) has cytotoxic activity and induction of apoptosis in breast cancer cells MCF-7 and HeLa cervical cancer cells. This study aims to determine the effects ofÃ‚Â PEE as an chemopreventive agent on rat liver cells induced 7,12-dimetilbenz[a]anthracene (DMBA). This study used Sprague Dawley strain female rats aged 40-50 days were divided into 5 groups : (1) DMBA control group, mice were induced with DMBA in per oral dose of 20 mg/kg; (2) DMBA + PEE dose 750 mg/kgBW group ; (3) DMBA + PEE dose 1500 mg/kgBW group ; (4) solvent control group of CMC-Na 0,5%; (5) PEE dose 1500 mg/kgBW control group. PEE was dissolved in CMC-Na 0,5% and administered daily, starting the seventh week after administration of DMBA. At the beginning ofÃ‚Â the tenth week of the study, rats were necropted and liver organs were isolated and stored in buffered formalin 4%. Qualitative analysis to determine the histopathology of liver cells through staining method of Hematoxyllin Eosin (HE), while quantitative analysis to determine the level of liver cell proliferation by AgNOR staining method. The results showed in the DMBA control group that liver cell morphology changes that hiperproliferation leading to carcinogenesis. In DMBA + PEE dose ofÃ‚Â 1500 mg/kgBW group improved the situation of DMBA-induced liver cells histopathology and antiproliferation activity better than DMBA + PEE dose of 750 mg/kgBW on DMBA-induced rat liver cells. The results showed that Physalis angulata L. herbs ethanolic extract can inhibit cell proliferation in rat liver caused by DMBA administration through antiproliferation mechanism and have potential for the development as chemoprevention material on liver cancer